The Prevalence of Degenerative Cervical Myelopathy-Related Pathologies on Magnetic Resonance Imaging in Healthy/Asymptomatic Individuals: A Meta-Analysis of Published Studies and Comparison to a Symptomatic Cohort. (May 2022) - Banerjee, Arkaprabha; Mowforth, Oliver D.; Nouri, Aria; Budu, Alexandru; Newcombe, Virginia; Kotter, Mark R.N.; Davies, Benjamin M.
Abstract: Degenerative cervical myelopathy (DCM) is a progressive cervical spinal cord injury brought about by mechanical stress from degenerative changes in the cervical spine. It is typically diagnosed on clinical symptoms and examination findings together with MRI findings. In this study, we explore the significance of these degenerative pathology to onset of DCM by performing the first meta-analysis on the prevalence of degenerative features reported on MRI amongst healthy and asymptomatic populations and compare this to the prevalence of degenerative features reported on MRI amongst a symptomatic population calculated in a previous review. We conducted a systematic review and meta-analysis in accordance with PRISMA guidelines, cognizant of their adaptation for epidemiological studies. A search strategy was used to identify original research carrying out MRI screening of cervical spines of asymptomatic patients in MEDLINE and Embase from 1985 to present day. The search yielded a total of 1098 studies of which 17 were included in this meta-analysis covering a total of 5059 patients. Ossification of posterior longitudinal ligament (pooled asymptomatic prevalence of 0.4%, 95% Confidence Interval [0.1%, 0.8%]), enlargement of ligamentum flavum (pooled asymptomatic prevalence of 11.8%, 95% Confidence Interval [5.3%, 18.4%]) and degenerative multilevel disc pathology (pooled asymptomatic prevalence of 64.5%, 95% Confidence Interval [48.3%, 80.8%], I 2 100%) were found to be significantly lower in asymptomatic populations. Symptomatic populations have a prevalence of 10.5% (95% Confidence Interval [7.7%, 13.3%]) for ossification of posterior longitudinal ligament, 56.8% (95% Confidence Interval [52.3%, 61.3%]) for enlargement of ligamentum flavum and 89.7% (95% Confidence Interval [86.9%, 92.5%]) for degenerative multilevel disc pathology [18]. Understanding the natural history of DCM is a recognised research priority, and whilst these perspectives require further evaluation, they may be of significant relevance to the evolving biomechanical understanding of the disease.